2000
DOI: 10.1001/archinte.160.10.1489
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Celiac Disease in Patients With Dyspepsia

Abstract: The present results indicate that the prevalence of CD in patients with dyspepsia is twice that of the general population. Thus, serological screening for CD should be considered in the early workup of these patients to allow diagnosis and treatment of an eminently treatable disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 34 publications
(44 reference statements)
6
43
1
5
Order By: Relevance
“…The question whether dyspeptic patients have an increased risk of CD has been previously assessed, with conflicting results (2,4,7,13) . Some limitations must be mentioned: some of these studies were underpowered or did not use a pre-specified definition of dyspepsia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question whether dyspeptic patients have an increased risk of CD has been previously assessed, with conflicting results (2,4,7,13) . Some limitations must be mentioned: some of these studies were underpowered or did not use a pre-specified definition of dyspepsia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence trying to assess the risk of CD among dyspeptic patients has been inconclusive, showing in some cases notorious discrepancies (2,4,7,13) . This may be due to methodological differences in the way they were designed.…”
Section: Introductionmentioning
confidence: 99%
“…We know that damages in gluten sensitivity are not confined to the small intestine (17) and no every gluten sensitive patients develop severe mucosal small bowel abnormality. Several studies have demonstrated that continues exposure to gluten may damage the structure and function of the gastric mucosa in gluten-sensitive patients (18,19). Other surveys indicate that approximately 20% of patients with dyspeptic symptoms have erosive esophagitis, 20% are estimated to have endoscopy-negative reflux disease , 1 0% have peptic ulcer, 2% h ave Barrett esophagus (20) and the results of the present study suggest that at least 2-3% coeliac disease with histology confirmation could be added to the list.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical forms of CD have increased considerably (7) and the presence of dyspepsia as a unique symptom has been frequently attributed to CD (8). In classical CD with prominent malabsorptive features, dyspepsia may be one of the symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation